2002
DOI: 10.1006/ceps.2001.1093
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Situational Interest: The Role of Gender and Skill

Abstract: Abstract:The purpose of this study was to examine individual and situational interests in learning motor skills as associated with gender and skill. Individual and situational interests and motor skill were measured in middle school girls (n = 109) and boys (n = 82). A correlation analysis for the entire sample showed a moderate correlation between skill and individual interest (r = .63) and weak relationships between individual and situational interest (r < .10) and between situational interest and skill (r <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 27 publications
6
42
1
10
Order By: Relevance
“…The findings, however, should be interpreted based on the sample limitation, which was predominantly African American. Although it has been reported that students' response to situational interest in physical education may be insensitive to certain demographic characteristics (Chen & Darst, 2002) Confirmatory factor analysis; all pathways are significant (Z scores > 1.96); SI = situational interest; AT = attention demand; CH = challenge; EX = exploration opportunity; EN = instant enjoyment; NO = novelty.…”
Section: Resultsmentioning
confidence: 89%
“…The findings, however, should be interpreted based on the sample limitation, which was predominantly African American. Although it has been reported that students' response to situational interest in physical education may be insensitive to certain demographic characteristics (Chen & Darst, 2002) Confirmatory factor analysis; all pathways are significant (Z scores > 1.96); SI = situational interest; AT = attention demand; CH = challenge; EX = exploration opportunity; EN = instant enjoyment; NO = novelty.…”
Section: Resultsmentioning
confidence: 89%
“…Situational interest is usually considered an affective state, triggered by the attractive, novel, and stimulating aspects of an object or environment (Krapp, Hidi, & Renninger, 1992). Situational interest influences learning by inducing stronger attention to learning materials (Hidi, 1995), and by increasing persistence in the task Chen & Darst, 2002). In the classroom, situational interest may be activated by the teacher, who manipulates some features of the instructional setting leading to students' positive response to learning (Bergin, 1999).…”
Section: Interest Research: An Overviewmentioning
confidence: 99%
“…Individual interest influences learning behavior and outcomes because it usually implies highly developed domain-specific knowledge. Thus, learners engaged with domain-specific activities related to their individual interest can rely on their knowledge to self-motivate and self-regulate learning (Chen & Darst, 2002;Hidi & Renninger, 2006;Renninger, 2000).…”
Section: Interest Research: An Overviewmentioning
confidence: 99%
“…With a middle school student sample (N = 191, 53% boys, 47% girls), Chen and Darst (2002) examined the extent to which individual and situational interests varied in terms of gender and motor skill performance levels. Individual interest was measured by asking students to rate on a 7-point, Likert-type scale their interest in basketball along with seven other physical activities.…”
Section: Research On Interest Constructmentioning
confidence: 99%